Hypertension secondary to renal hypoplasia presenting as acute heart failure in a newborn - Jena Deitrick; Kayle Stevenson; Daniel Nguyen; William Sessions; Vijay Linga; Tetyana Vasylyeva (BMC, 2019)
Abstract Introduction Neonatal hypertension is defined as persistent systolic and/or diastolic blood pressures above the 95th percentile compared to other infants of similar gestational age and size. Neonatal hypertension is a rare condition, occurring in only 0.2-3.0% of neonates. The most common etiology of neonatal hypertension is renal vascular or parenchymal disease, and it is usually detected on routine examination in an asymptomatic child. However, it may present in a variety of manners, including acute heart failure, renal dysfunction, feeding difficulties, failure to thrive, tachypnea, apnea, lethargy, irritability, or seizures. Case presentation A term female was born via repeat caesarean section with vacuum extraction. On day of life (DOL) 3, the baby presented to the emergency department with poor feeding and lethargy. Initial laboratory tests indicated severe metabolic acidosis and the patient was transferred to our neonatal intensive care unit (NICU). During the hospital stay, the patient had intermittently high blood pressures. An echocardiogram was ordered, which demonstrated a severely decreased ejection fraction of 33%, but no signs of coarctation of the aorta. The low ejection fraction and constellation of symptoms were consistent with the diagnosis of acute heart failure, so treatment with milrinone was initiated. Further labs demonstrated elevated renin and aldosterone, and a computed tomography scan showed right kidney hypoplasia with reduced perfusion. This suggested a renovascular etiology of hypertension causing the initial presentation of acute heart failure. The patient was started on enalapril and clonidine for blood pressure control and was discharged with a home blood pressure monitoring system. At 5 months of life, this patient was still on enalapril and amlodipine as well as home blood pressure monitoring. Conclusions Acute heart failure is a rare presentation of neonatal hypertension, and prompt recognition and treatment for the underlying systemic hypertension is necessary to provide the best possible outcomes for patients. Due to the lack of sufficient evidence, treatment of hypertension in newborns is often anecdotal in nature. Further awareness of neonatal hypertension and research determining ideal methods of diagnosis and treatment would benefit physicians and their affected patients.